Constructivist Classroom Activities for Biology Learning - Dogra, Bharti (JOURNAL OF INDIAN EDUCATION, 2010)
There are many learning theories which we study under Educational Psychology. Constructivism is one of them which focus on developing the learners‘knowledge by constructing the world around them through experience, observation, documentation, analysis and reflection. In the classrooms of today, learners are no longer passive recipients nor are the teachers ‘givers of information, knowledge and wisdom’. According to constructivist perspective, the teaching or rather more precisely learning of biology is not the search for the ultimate truth. It is the process which is of utmost importance in biology than the content. So when the learning of biology involves active construction of knowledge by children, then the classroom environment must call for more synergies rather than mere individual participation. The teachers need to develop the ability to work with children creatively to generate new ideas, new theories, new products and new knowledge. The engagement of the learner in the construction of classroom activity requires inputs from a reflective teacher and meticulous pre-planning before a unit is transacted in the class. Strategies of peer learning through group work and whole class work are important, again depending on task and the teaching objective. Learner autonomy and respect for individual learner is mandatory if real learning is to take place. Encouraging learners to reflect and question their own understanding further aids comprehension. This paper discusses some classroom activities which encourage thinking, understanding, exploration, problem solving, collaboration, analysis, observation and prediction for Biology learning.